A novel approach for modulating the spatial distribution of fat globules in acid milk gel and its effect on the perception of fat-related attributes. (February 2021) - Cheng, Weihua; Liu, Hongna; Shen, Qingwu; Liu, Chengguo; Zhou, Hui; Luo, Jie
Graphical abstract: Highlights: Acid milk gels with inhomogeneous fat spatial distributions were prepared. Two gels made from the same milk were superimposed to form a new gel. Superimposed gels exhibited higher average area fractions of fat on the surfaces. Superimposed gels exhibited greater differences in fat content between layers. Superimposed gels had lower friction coefficients and higher creaminess ratings. Abstract: Modulating the inhomogeneous distribution of fat globules within an emulsion gel is now being considered an effective method to increase the perception of fat-related sensory attributes. However, the methods for preparing the inhomogeneous gel were relatively complicated in previous studies. In the present study, milks enriched with different sizes of fat globule were obtained and then used to prepare glucono-δ-lactone-induced milk gels. The gels with different spatial distributions of fat globules were obtained through natural creaming. To ensure the high fat content layer exist on the gel surface, the two gels made from the same milk were superimposed from the bottom to form a new gel. In situ confocal microscopy showed that under the same overall fat content, the superimposed gel containing larger fat globules (L-L gel) exhibited the greatest inhomogeneity in microstructure with the highest average surface fat area fraction (10.9%), and the largest difference in fat content between the surface and the inside layers (9.1%). To illustrate the effect of inhomogeneous distribution of fat globules in gels on the perception of fat-related attributes, quantitative descriptive sensory analysis as well as the lubrication properties measurement under simulated oral processing conditions were carried out. The results showed the superimposed gels exhibited higher creaminess ratings and lower friction coefficients at 20 mm/s than those of the original gels. Overall, the study modulated the spatial distribution of fat globules in acid milk gels through natural creaming and superimposition and illustrated its positive effect on the perception of fat-related sensory attributes.